Enhancing performance of grid-connected photovoltaic systems based on three-phase five-level cascaded inverter - Marwan E. Ahmad; Ali. H. Numan; Dhari Y. Mahmood (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Multilevel inverters play an important role in power converters due to their good advantages. The cascaded H-bridge inverter is one of the most prominent and most suitable multilevel inverters in PV systems. Each H-bridge has a separate photovoltaic (PV) array as an independent direct current (DC) source. This paper introduces a three-phase cascaded H-bridge inverter with five levels connected to the grid to improve the performance and efficiency of the photovoltaic system. In the proposed system, each PV group has MPPT to extract the maximum power point from the PV group at certain irradiation and temperature and also to mitigate the mismatch that causes in the imbalance transmitted power from inverter to the main grid. The proposed control scheme with modulation compensation was used, and the system was simulated in MATLAB/Simulink with two different scenarios. The simulation results demonstrate the effectiveness of the proposed connection in minimizing the total harmonic distortion (THD) to acceptable limit, low overshoot, and fast-tracking to the desired value.